Anti-gastritis and wound healing effects of Momordicae Semen extract and its active component. (February 2013) - Jung, Kiwon; Chin, Young-Won; Chung, Yoon Hee; Park, Yang Hae; Yoo, Hunseung; Min, Dong Sun; Lee, Bongyong; Kim, Jinwoong
<x xml:space="preserve">Abstract</x> Momordicae Semen, Momordica cochinchinensis Springer (Cucurbitaceae), has long been known to effectively relieve boils, rheumatic pain, and hemorrhoids. In this study, we investigated whether Momordicae Semen extract (MSE) has anti-gastritis effects in various rodent models and also explored possible mechanisms for the gastroprotective effects of MSE. MSE provided remarkable protective effects, comparable to those of rebamipide, in ethanol- and diclofenac-induced acute gastritis. In addition, it has demonstrated protective effect in a Helicobacter pylori-insulted chronic gastritis model. MSE also showed wound healing effect on cutaneous injury of mice and stimulated calcitonin gene-related peptide and somatostatin receptors, which may be related to its anti-gastritis effects. In a single oral dose toxicity study, the approximate lethal dose of MSE was determined at >2000 mg/kg/day. The NOAEL was set to be 2000 mg/kg/day from the repeated oral dose toxicity study. Moreover, momordica saponin I, a major ingredient of MSE, treatment decreased gastric mucosa damage indices in the ethanol- and diclofenac-induced acute gastritis models. The results suggest that MSE could be a promising gastroprotective herbal medicine and momordica saponin I might be used as an active marker compound for MSE.